MSG 489 - Numerical Methods For Differential Equations February 2020 - PPSM, Pusat Pengajian Sains Matematik (Universiti Sains Malaysia, 2020)
Please check that this examination paper consists of THREE (3) pages of printed material before you begin the examination. Instructions : Answer FOUR (4) questions.